The Role of Assets Tangibility, Firm Size, and Macroeconomic Factors on Stock Returnin Nepalese Hydropower Companies - Ajay Kumar Khadka; Surya Devkota; Bhupendra Jung Shahi; Kapil Sah (Pravaha, 2023)
The purpose of this study was to evaluate the influence of the inflation rate, foreign exchange rate, firm size, gross domestic product, and assets tangibility on stock returns in the hydropower sector.For the 2016/17-2022/23 period, secondary data from five listed Nepalese hydropower companies (Butwal Power Company Limited, Api Power Company Limited, Chilime Hydropower Company Limited, Arun Valley Hydropower Development Company Limited, and Barun Hydropower Company Limited) were analyzed using a descriptive and causal-comparative research design. The study employed correlation analysis, multiple regression analysis, and the mean to investigate the relationships and effects of these variables on stock returns. The findings show that the asset's tangibility and firm size do not significantly affect stock returns.As a result, the inflation rate and foreign exchange rate have significant impacts on returns on stocks, with inflation having an adverse effect and the foreign exchange rate having a positive impact. These results show the influence of macroeconomic factors in determining stock performance. Companies should incorporate these economic indicators into their strategic planning to more effectively determine financial risks and improve stock performance, while policymakers should focus on stabilizing inflation and managing currency fluctuations to improve market conditions.